Методические указания по поиску в электронном каталоге - Чуприкова Н. Т. Наталья Трофимовна; Котова И. В. Ирина Владимировна; Халошина О. В. Ольга Владимировна (Томск, [Б. и.], 2009)
Заглавие с титульного экрана